Prospects of the Russian Federalism Development - Kovaleva, Margarita (Administrative consulting, 2019)
In the article, the analysis of the Russian federalism is carried out, problems and the prospects of development are defined. Development of federalism in Russia defines development of economic, political and social spheres of each region, ensures the state integrity and safety of the country. Purpose: to study features of the Russian federalism and the prospects of its development. Methods: dialectic logic, comparative and legal, formal and logical. Results: the analysis of stages of development of the Russian state, the legislation and practice of implementation of the Constitution of the Russian Federation showed that the Russian federalism changed and developed, were improved the relations between Federation and subjects, however problems of the constitutional regulation of federalism in Russia still remain. Conclusions: for development of the Russian federalism has increase in an initiative of regional public authorities in the solution of all-federal questions, it is necessary to regulate their powers in adoption of nation-wide decisions, to define the centers of responsibility of subjects, to develop institute of federal responsibility in general. The prospects of development of the Russian federalism consist in the constitutional fixing of bases of the federal relations, respect for human rights, optimization of the financial relations between subjects, strengthening of economic bases of the Russian federalism.